Attitude and impact changes of hijab wearing among Muslim Malay women in Malaysia - A.Manaf, Aini Maznina; Wok, Saodah; Ismail, Rizalawati (University of Padjajaran, 2014)
Hijab wearing is a common phenomenon in Malaysia. Many Malay women choose to wear hijab and women with headcover becomes an identity of Malay Muslim women in this country. In fact, the number of women who is wearing hijab in Malaysia is gradually increasing as time changes. Many studies (Williams & Vashi, 2007; Furseth, 2011) were carried out to understand the factors that influence hijab wearing among Muslim women. Despite the obligation for a Muslim women to wear hijab, not much effort done by scholars to examine the attitude and perception of Malay Muslim women in Malaysia on hijab-wearing. This paper examines the perception and attitude of Malay Muslim women in Malaysia on hijab wearing and the impact changes on their practices. The specific obejectives of the study are (a) to explore the perception and attitude towards hijab wearing among Malay Muslim women; and (b) to investigate the impact changes of hijab wearing on Malay Muslim women. This study tests the application of Cognitive Dissonance Theory (Festinger, 1957) on hijab wearing among Malay Muslim women in Malaysia. This study employs a quantitative research design whereby questionnaire was used as the survey research instrument to collect data. Out of 796 Malay women surveyed, the results showed that the respondents have a good perception on hijab wearing. The findings also shows that Malay Muslim women in Malaysia have a good attitude towards hijab wearing. Although perception and attitude towards hijab wearing contribute to the impact changes among Malay Muslim women in Malaysia, the earlier has a higher predictor than perception. Hence, it can be concluded that a good perception and positive attitude towards hijab wearing is able to bring some impact changes on their practices. Therefore, it can be concluded that to a certain extent, Cognitive Dissonance Theory holds true for hijab wearing practices among Malay Muslim women in Malaysia.